Family Time Negotiations in the Context of Non-Standard Work Schedules. (30th March 2019) - Tammelin, Mia; Mykkänen, Johanna; Sevón, Eija; Murtorinne-Lahtinen, Minna; Rönkä, Anna
Abstract : Present-day parenting is centred round the question of time, especially in the case of working parents. This study analysed negotiations over time in families where one or both parents work non-standard schedules, that is, during evenings, nights and weekends. We asked what aspects of time are negotiable and with whom, and who in the family bears the ultimate responsibility for these negotiations. The analysis was based on interviews with 47 people conducted in 2013 in Finland. The findings indicated that time negotiations within the family concerned everyday routines and schedules, social life and the family's philosophy. Family life and schedules in the context of non-standard schedules were often subject to moralising remarks from others, including close relatives and friends. Parents seemed to have some room to negotiate on the timing of their work schedules with their employers. Men and women differed in the positions they adopted in time negotiations: women took an active 'I' perspective, while men took a more passive spousal perspective. This result shows that traditional gender differences continue to prevail.